New records for the flora of Veracruz in the Cañón del Río Blanco National Park, Mexico - Vargas Rueda, Abel Felipe; Rivera Hernández, Jaime Ernesto; Cházaro Basáñez, Miguel De Jesús; Alcántara Salinas, Graciela (Instituto de Ecología, A.C., 2018)
Background and Aims: With only a few explorations since the 19th century and isolated plant vouchers, the Cañón del Río Blanco National Park has been little explored from the floristic point of view; however, new records for the flora of the state of Veracruz, Mexico, have been documented in the polygonal covered by this Natural Protected Area. The aim of this study is to present the novelties that this site contributes to this flora.Methods: Botanical expeditions were carried out in two different periods: the first between 2012 and 2014 and the second in 2016. Specimens were collected and photographed, and taxonomic determination with specialized literature was executed. Finally, the specimens were deposited in the Mexican herbaria CORU, MEXU and XAL.Key results: Manfreda verhoekiae (Asparagaceae), Cypripedium molle (Orchidaceae), Goodyera brachyceras (Orchidaceae), Krameria pauciflora (Krameriaceae) and Crusea psyllioides (Rubiaceae) are reported as new records for the flora of Veracruz, whereas Dioscorea orizabensis (Dioscoreaceae) and Nectouxia formosa (Solanaceae) are rediscoveries for the same flora.Conclusions: The theory regarding floristic affinity of vegetation of this semiarid region of Veracruz with the flora of the Tehuacán-Cuicatlán Valley is reinforced. It is suggested to continue botanical explorations within this Natural Protected Area.